Crooked river eaudiobook - Preston, Douglas (Pendergast, 2020)
From the #1 New York Times bestselling authors: Racing to uncover the mystery of several severed feet found floating in the Gulf of Mexico, Agent Pendergast is faced with the most inexplicable challenge of his career. A startling crime with dozens of victims . Appearing out of nowhere to horrify the quiet resort town of Sanibel Island, Florida, dozens of identical, ordinary-looking shoes float in on the tide and are washed up on the tropical beach—each one with a crudely severed human foot inside. A ghastly enigma with no apparent solution . Called away from vacation elsewhere in the state, Agent Pendergast reluctantly agrees to visit the crime scene—and, despite himself, is quickly drawn in by the incomprehensible puzzle. An early pathology report only adds to the mystery. With an ocean of possibilities confronting the investigation, no one is sure what happened, why, or from where the feet originated. And they desperately need to know: are the victims still alive? A worthy challenge for a brilliant mind . In short order, Pendergast finds himself facing the most complex and inexplicable challenge of his career: a tangled thread of evidence that spans seas and traverses continents, connected to one of the most baffling mysteries in modern medical science. Through shocking twists and turns, all trails lead back to a powerful adversary with a sadistic agenda and who—in a cruel irony—ultimately sees in Pendergast the ideal subject for their malevolent research.